Arterial stiffness and hypertension status in Afro-Caribbean men. Issue 3 (March 2019) - Kuipers, Allison L.; Miljkovic, Iva; Barinas-Mitchell, Emma; Cvejkus, Ryan; Bunker, Clareann H.; Wheeler, Victor W.; Zmuda, Joseph M.
Abstract : Objective: African ancestry individuals are at high risk for hypertensive cardiovascular disease (CVD) and could benefit from early detection of arterial stiffening. We tested the association between the 2017 ACC/AHA hypertension categorizations, which include new blood pressure (BP) cutoffs and a definition for elevated BP, and arterial stiffness in 772 Afro-Caribbean men aged 50+ years (mean 64 years). Methods: Arterial stiffness was assessed by brachial–ankle pulse-wave velocity (PWV) using a waveform analyzer. Hypertension groups were based on the 2017 ACC/AHA guidelines and by pharmacologic control status. Multiple linear/logistic regression was used to determine the association of PWV with BP and hypertension. Results: Mean (SD) PWV was 1609 (298) cm/s and was independently correlated with age, SBP, pulse, diabetes, height, and alcohol intake (all P < 0.02). After adjusting for these, in men aged at least 65 years, those with stage 1 or uncontrolled stage 2 hypertension had significantly greater PWV than all other groups (all P < 0.05). Men with controlled hypertension had similar PWV to those with elevated BP ( P = 0.7); however, this was significantly greater than men with normal BP (all P < 0.05). Patterns were similar, but with smaller effect sizes, in men aged less than 65 years (all P < 0.05 except controlled hypertension versus elevated or normal BP were not significant). Conclusion: In these high-risk Afro-Caribbeans: stage 1 hypertension is associated with increased PWV, which supports the new guidelines; and, pharmacologic control appears to partially protect men from increased PWV. Longitudinal studies are needed to determine optimal PWV and timing of antihypertensive treatment for preventing future CVD. Abstract : Supplemental Digital Content is available in the text